An investigation of solar radio noise in relation to visible phenomena - Poole, Lex Martin Graham (Rhodes University, Faculty of Science, Department of Physics, 1961)
The work of previous writers on the origin and propagation of solar radio noise, and particularly the correlation with visual events is reviewed, and then the construction of the author's 300 Mc/s receiver described. With a view to the author's project, absorption of electromagnetic radiation in the solar corona is quantitatively discussed, and a method for determining the intensity without absorption of a radio burst is evolved. The main project involves briefly the discovery of any possible relationship between the magnitude of a visual flare and the corrected intensity of an associated radio burst as measured at 125 Mc/s. It is concluded that no definite relation exists, but from this consideration an approximate shape of the instantaneous frequency profile of outburst elements is obtained. An extension of the theory to isolated bursts enables us to predict both this bandshape, and the velocity of an exciting agency moving radially through the corona.
Keywords: Solar radio emission; Radio astronomy -- Instruments